Implementasi Lean Warehouse terhadap Produktivitas Operasional Pengiriman di PT. ABC - Fadila Ainur Rahma; Ma’ruf Ma’ruf; Wenny Ananda Larasati (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the level of lean warehouse implementation and the dominant aspects that can affect the productivity of shipping operations at PT. ABC. The approach adopted in this study is quantitative descriptive by distributing questionnaires to respondents involved in shipping operations both in administration and in the field. The results obtained that the level of lean warehouse implementation reached 55.17%, which indicates that most lean warehouse aspects have been implemented but are not optimal in some aspects. The dimensions of motion, waiting, overprocessing, transportation, and flow management are still in the "less good" category, while defects and HRM are classified as "good". This condition is at the level of shipping operational productivity which only reached 53%. The lean warehouse aspects that most dominantly affect productivity are waiting and motion, which are related to punctuality as well as the arrangement and quantity of work in the warehouse. This study provides recommendations for improving lean warehouse implementation, especially in dimensions that are still less than optimal. Improving process arrangement and reducing waiting time will increase overall efficiency and productivity, thereby influencing company performance in achieving better operational goals.